2021
DOI: 10.1145/3487567
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Cities: Software Developers Working from Home during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has shaken the world to its core and has provoked an overnight exodus of developers who normally worked in an office setting to working from home. The magnitude of this shift and the factors that have accompanied this new unplanned work setting go beyond what the software engineering community has previously understood to be remote work. To find out how developers and their productivity were affected, we distributed two surveys (with a combined total of 3,634 responses that answered all r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…There are lately several research projects that study the impact of the COVID-19 pandemic on the way software developers work [44]- [47]. These papers try to relate practices adopted because of the pandemic, especially Working From Home (WFH), with the productivity and the well-being of software developers working on the usual software projects.…”
Section: Related Workmentioning
confidence: 99%
“…There are lately several research projects that study the impact of the COVID-19 pandemic on the way software developers work [44]- [47]. These papers try to relate practices adopted because of the pandemic, especially Working From Home (WFH), with the productivity and the well-being of software developers working on the usual software projects.…”
Section: Related Workmentioning
confidence: 99%
“…However, there is a statistical difference between respondents who are in a small team and those in a large team. [10]. The authors reported a mixed experience for software engineers when working from home, and for the same factor, one engineer can perceive a benefit and another can perceive it as a challenge.…”
Section: Po4 Po5 Po6mentioning
confidence: 98%
“…They concluded that perceived productivity has declined (admitting a marginal effect size) as a result of negatively affected well-being and that organizations need to accept that expecting normal productivity under crisis circumstances is unrealistic. Ford et al conducted a two-wave study on productivity in Microsoft [10]. Both surveys indicated that the productivity increased among some participants and stayed the same or decreased among the others, which led the authors to conclude that the productivity during the COVID-19 pandemic was dichotomous.…”
Section: Work From Home and Software Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…A key question regarding exclusively-digital labor is whether a completely online workplace improves working conditions, particularly for those from marginalized socio-demographic and/or labor groups. Prior work has studied the experiences of office workers in formal labor arrangements switching to remote work during the pandemic [46,29,99,20,44,39,147] and the experiences of gig workers (who are part of the informal labor sector) who conduct digitally-mediated in-person work [31,106,105,8,102]. However, to our knowledge, no prior work has studied the experiences of informal labor sector workers who switched from in-person work to completely digital work, while continuing to do the same type of work.…”
Section: Introductionmentioning
confidence: 99%